Interference screws vs. suture anchors for isolated medial patellofemoral ligament femoral fixation: A systematic review - Filippo Migliorini; Alice Baroncini; Jörg Eschweiler; Markus Tingart; Nicola Maffulli (Elsevier, 2022)
Purpose: The present study aimed to systematically review and compare 2 femoral autograft fixation techniques, namely, interference screws and suture anchors, for isolated medial patellofemoral ligament reconstruction in patients with recurrent patellofemoral instability at mid- to long-term follow-up. Methods: A literature search was performed in September 2020. All studies reporting the outcomes of primary isolated medial patellofemoral ligament reconstruction for recurrent patellofemoral instability were considered for inclusion. Only studies reporting the type of femoral autograft fixation under examination were considered. Studies reporting data from patients with elevated tibial tuberosity-tibial groove, patella alta, and/or Dejour's trochlear dysplasia types C and D, were not included. Only articles reporting data with a minimum follow-up period of 18 months were considered. Results: Data from 19 studies (615 patients) were retrieved. The overall age was 24.4 ± 6.7 years (mean ± SD). The mean follow-up was 46.5 ± 20.9 months. There were 76 patients in the anchor group and 539 in the screw group. Comparability was found with regard to age and follow-up duration between the 2 study groups. There was comparability between the Kujala, Lysholm, and Tegner scores at baseline. At the last follow-up, no worthy differences were found in terms of mean Kujala (+2.1%; p = 0.04), Lysholm (+1.7%; p = 0.05), and Tegner (+15.8%; p = 0.05) scores. Although complications occurred almost exclusively in the screw cohort, no statistically significant difference was found. Conclusion: Femoral autograft fixation through interference screws or suture anchors report similar clinical scores and rate of apprehension test, persistent joint instability, re-dislocations, and revisions. These results must be interpreted within the limitations of the present study.